2022
DOI: 10.3390/cells11050797
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondria in Human Fertility and Early Embryo Development: What Can We Learn for Clinical Application of Assessing and Improving Mitochondrial DNA?

Abstract: Mitochondria are well known as ‘the powerhouses of the cell’. Indeed, their major role is cellular energy production driven by both mitochondrial and nuclear DNA. Such a feature makes these organelles essential for successful fertilisation and proper embryo implantation and development. Generally, mitochondrial DNA is exclusively maternally inherited; oocyte’s mitochondrial DNA level is crucial to provide sufficient ATP content for the developing embryo until the blastocyst stage of development. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 109 publications
(332 reference statements)
1
17
0
Order By: Relevance
“…It has been reported that mitochondria have a significant contribution to regulating the various physiological aspects of reproductive processes. Normally functioning mitochondria and intact mitochondrial membrane potential are a pre-requisite for normal sperm motility (Piomboni et al, 2012;Dutta et al, 2019;Ribeiro et al, 2021), hyperactivation (Dutta et al, 2019), capacitation (Jha et al, 2003;Bailey, 2010;Aitken, 2017;Dutta et al, 2019), acrosin activity (Breitbart, 2003), acrosome reaction (Breitbart, 2003;Gupta and Bhandari, 2011)and DNA integrity (Sakkas and Alvarez, 2010;Mallidis and Wistuba, 2018;Durairajanayagam et al, 2021;Podolak et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that mitochondria have a significant contribution to regulating the various physiological aspects of reproductive processes. Normally functioning mitochondria and intact mitochondrial membrane potential are a pre-requisite for normal sperm motility (Piomboni et al, 2012;Dutta et al, 2019;Ribeiro et al, 2021), hyperactivation (Dutta et al, 2019), capacitation (Jha et al, 2003;Bailey, 2010;Aitken, 2017;Dutta et al, 2019), acrosin activity (Breitbart, 2003), acrosome reaction (Breitbart, 2003;Gupta and Bhandari, 2011)and DNA integrity (Sakkas and Alvarez, 2010;Mallidis and Wistuba, 2018;Durairajanayagam et al, 2021;Podolak et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Cell and Developmental Biology frontiersin.org 2011; Aitken, 2017;Dutta et al, 2019;Ribeiro et al, 2021;Podolak et al, 2022) for semen quality and human sperm function in fertilization. However, the precise role of mitochondria in spermatozoa remains to be fully explored.…”
Section: The Redox Balance Of Cytochrome In the Midpiece Region Of Mi...mentioning
confidence: 99%
“…The control of reproductive behavior is tightly linked to the functional cellular/tissue mechanisms associated with energy metabolism and food availability [59,98,122,[183][184][185]. As reproductive behavior and physiology are tightly controlled at certain points in the lifespan, it is not surprising that the broader relaxin system likely intersects with this aging-reproduction nexus.…”
Section: Reproductive Agingmentioning
confidence: 99%
“…Mitochondrial DNA contains 37 genes, all of which are essential for normal mitochondrial function. Thirteen encoded proteins are involved in oxidative phosphorylation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%